Investigation into the effect of beam shape on melt pool characteristics using analytical modelling - Ahmed, N.; Voisey, K.T.; McCartney, D.G. (Elsevier, 2010)
An established analytical model is used to simulate an extended laser beam. Multiple Gaussian sources are superimposed to form a rectangular beam and results are compared with a single circular Gaussian source model as well as experimental results from a high power diode laser with a rectangular beam. Melt depth, and melt pool profile and progression have been predicted by modelling which are compared with experimental results from melting of Inconel 625. The model produced is shown to give a reasonable prediction of melt pool shape and can be usefully employed to help optimise overlap required for laser surface processing applications. The value of absorptivity used in the model can be used as a fitting parameter to optimise the match between experimental and predicted results.